Role of Learning Discipline in Mediating The Influence of Parent’s Parenting Towards Student’s Learning Achievement (Journal of Primary Education, 2018)
The increasing of learning achievement is affected by internal and external factors. These factors are parent’s parenting and learning discipline. This research aims to analyze the role of learning discipline in mediating the effect of parent’s parenting towards student’s learning achievement. Population in this research is fifth-grade elementary students in the district of Kebonagung, Demak in year 2017/2018. The sampling technique used is random cluster sampling with two-stage cluster sampling. Data collection in this research use questionnaire, documentation, and observation of student’s learning discipline. The analysis result stated that there is the positive and significant effect of parent’s parenting through learning achievement (50.9%); learning discipline through student’s learning achievement (37.7%); and parent’s parenting through learning discipline (67.7%). We also found that there is an impact of learning discipline as the mediation of parent’s parenting through learning achievement (25.4%). This finding lead parent’s to more responsive towards problems that associated with parent’s parenting and learning discipline.